Effect of tool pin profile on the microstructure and mechanical properties of friction stir processed Al6061/Al2O3-TiB2 surface hybrid composite layer - Khojastehnezhad, Vahid M.; Pourasl, Hamed H.; Barenji, Reza Vatankhah (Sage Publications Ltd, 2019)
The Al6061/Al2O3-TiB2 surface hybrid composites were produced using friction stir processing. The effect of the tool pin profile was investigated on the microstructure and mechanical properties including hardness and wear resistance. For this purpose, simple cylindrical, threaded cylindrical, taper, square, and triangular pin profiles were used. X-ray diffraction analysis and transmission electron microscopy were used to characterize the used powder. Light and scanning electron microscopes were utilized for the microstructural observations of the processed samples. The results showed that the distribution of Al2O3-TiB2 particles in the specimens produced using square and triangular tool pin profiles was more uniform due to their tool geometry, which results in better stirring of the material and good material flow. Consequently, a greater reduction of particle clustering was observed, and hence the mechanical properties were enhanced. Moreover, the samples produced using square and triangular pin profiles exhibited more grain refinement than the other samples. More uniform structure, less clustering, and finer grains produced by square and triangular pin profiles caused higher hardness and wear resistance of the samples.
Keywords: Friction stir processing; hybrid composite layer; Al2O3-TiB2; tool pin profile